Getting Africa hooked on fish farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Fish is a popular part of the diet in most ACP countries. It has long been termed 'the poor man's protein' and the overall demand for fish is increasing as populations grow and rising standards of living in urban areas lead to expectations for diets...